2021
DOI: 10.47102/annals-acadmedsg.2021255
|View full text |Cite
|
Sign up to set email alerts
|

Does pulmonary metastasectomy of colorectal metastases translate to better survival? A systematic review

Abstract: Introduction: Surgical resection of the primary and metastatic tumour is increasingly recommended in suitable patients with metastatic colorectal cancer (CRC). While the role of metastasectomy is well studied and established in colorectal liver metastasis, evidence remains limited in pulmonary metastases. This systematic review was conducted to examine the current evidence on the role of lung metastasectomy (LUM) in CRC. Methods: Three databases were systematically searched, to identify studies that compared s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…There is also no consensus on chemotherapy and length of surveillance before pneumonectomy. Furthermore, the effect of lung metastasectomy on outcomes is controversial in metastatic CRC (18). Given that there are cases of cured patients such as case 2 in the present report, pneumonectomy should be considered if technically and physically feasible.…”
Section: Discussionmentioning
confidence: 88%
“…There is also no consensus on chemotherapy and length of surveillance before pneumonectomy. Furthermore, the effect of lung metastasectomy on outcomes is controversial in metastatic CRC (18). Given that there are cases of cured patients such as case 2 in the present report, pneumonectomy should be considered if technically and physically feasible.…”
Section: Discussionmentioning
confidence: 88%
“…Several retrospective studies support the use of pulmonary metastasectomy as a standard of care in metastatic CRC ( 6 ) but some do not show clear survival benefits at present ( 7 ). Our study found a five-year OS of 33.2%, which is within the range of OS in such cases described in the literature (27%–68%) ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies support the use of pulmonary metastasectomy as a standard of care in metastatic CRC (6) but some do not show clear survival benefits at present (7).…”
Section: Discussionmentioning
confidence: 99%
“…Their results support the use of SBRT in this cohort of patients as it was associated with a delay in progression to polymetastatic disease. Further prospective studies are necessary to obtain a better understanding of the long-term effect of lung metastasectomy in metastatic colorectal cancer [ 83 ].…”
Section: Contemporary Management Strategiesmentioning
confidence: 99%